IDENTIFIKASI KEBERADAAN BENDA ASING PADA AREA PENGUKURAN TOMOGRAFI DENGAN MENGGUNAKAN METODA ELECTRICAL IMPEDANCE TOMOGRAPHY (EIT) BERBASIS LABVIEW - Endang Wijaya; Sastra Kusuma Wijaya (Politeknik Negeri Jakarta, 2018)
ABSTRACTEIT (Electrical Impedance Tomography) is one of several tomographic methods to estimate impedance distribution in a domain based on the measurement of a boundary area in a certain area. This method is widely used to observe the presence and growth of foreign matter in the area observed, such as cancer in the breast.In this study an instrument was designed to identify the presence and geometry of foreign objects, which were placed in the area of tomography measurement (phantom) in the form of three-dimensional (3D) images, Data acquisition instrument uses NI USB 6351 and LabVIEW (hard & software), with l testing and analysis of 3D image reconstruction using a modeling algorithm